Deadly drama! - Cole, Stephen; Fox, Woody (Red Fox London, 2009)
Young Teggs Stegosaur is a pupil at Astrosaurs Academy - where dinosaurs train to be Astrosaurs. The Academy is set to feature in an amazing mega-movie and Teggs and his friends have starring roles. But while shooting the action scenes, mysterious mishaps put the cadets in danger.